Employee Engagement in Public and Private Banks in Four Cities of North India - Praapti Arya, Stephen Das, Amita Maxwell (Mathematical Statistician and Engineering Applications, 2022)
The purpose of this research was to identify the explore the differences in the typical levels of involvement in public and private banks. Second, there is a notable gap in the degrees of participation at various organisational tiers banking institutions located in four cities of North India. A terrific relationship with the workforce is at the heart of employee engagement. Each company’s human resources are its most precious and crucial assets. Organization should to maximise wealth through maximising its human capital. Employee Engagement at Work is a dependent variable, whereas other research variables include several forms of Personal Empowerment components (Access to Training & Career Opportunities, Workplace Culture, Organizational Communication, Leadership, Work/ life Balance) as independent variables. It’s ironic that in the pursuit of wealth maximisation, people are often overlooked or treated as expendable. Previously utilised, high-quality surveys were repurposed to acquire the necessary data. Then, questionnaires were implemented using Pilot-Study approach and Cronbach alpha acquired. The research adds a new dimension to the idea of employee involvement in financial institutions by placing the emphasis on the employees rather than the customers. The purpose of this study is to shed some insight on the numerous factors that influence employee engagement in private and public sector Banks in Andhra Pradesh. SPSS has been used to analyse the data by computing the average, standard deviation, skewness, and kurtosis. All study hypotheses were supported by the data, as determined by the results of hypothesis testing at the 95% confidence level.